Analisis Persaingan Bisnis Pasar Tradisional Wonokusumo Surabaya Dengan Pasar Online Platfrom Shopee: Perspektif Mekanisme Pasar dalam Islam - Silfi Qotrun Nahda; Aslikhah; Sukamto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The Impact of Technology on Shopping Behavior and the Competition between Traditional Markets and Shopee Technological advancements, particularly in the current digital age, have significantly impacted people's lifestyles, including their shopping habits. The emergence of e-commerce and online platforms like Shopee has transformed the way consumers purchase goods and has also affected the existence of traditional markets. In this context, the competition between traditional markets and Shopee has become increasingly fierce, with diverse consequences for businesses in both markets. Business competition involves sellers vying for profit, market share, and sales volume. Typically, sellers strive to outperform competitors by differentiating their prices, products, distribution channels, and promotional strategies. In Islam, competition is permissible, but it should be conducted ethically and fairly. This research employs a descriptive qualitative method to analyze the dynamics of competition between Wonokusumo Traditional Market in Surabaya and the online platform Shopee. It further investigates the impact of Shopee's presence on the traditional market and its vendors and aims to identify solutions that can enhance the sustainability of traditional markets amidst the competition with e-commerce.